Regulation of hepatitis C virus replication by the core protein through its interaction with viral RNA polymerase - Kang, Su-Min (Biochem Biophys Res Commun, 2009)
The hepatitis C virus (HCV) core protein is a structural component of the nucleocapsid and has been shown to modulate cellular signaling pathways by interaction with various cellular proteins. In the present study, we investigated the role of HCV core protein in viral RNA replication. Immunoprecipitation experiments demonstrated that the core protein binds to the amino-terminal region of RNA-dependent RNA polymerase (RdRp), which encompasses the finger and palm domains. Direct interaction between HCV RdRp and core protein led to inhibition of RdRp RNA synthesis activity of in vitro. Furthermore, over-expression of core protein, but not its derivatives lacking the RdRp-interacting domain, suppressed HCV replication in a hepatoma cell line harboring an HCV subgenomic replicon RNA. Collectively, our results suggest that the core protein, through binding to RdRp and inhibiting its RNA synthesis activity, is a viral regulator of HCV RNA replication.